Impression Management in Graphical Representation of Economic, Social, and Environmental Issues: An Empirical Study - Cuere, Tuvana; Esen, Emel; Ozsozgun Caliskan, Arzu (MDPI, 2020)
Due to the increasing sustainability concerns among society and investors, companies share information demonstrating their social and environmental impacts to make an impression in corporate reports. Thus, impression management is used to influence company stakeholders' perception of their performance through graphs. Graphs presented in corporate reports are powerful impression management tools which communicate performance-related messages to the stakeholders. The purpose of this study is to examine the use of graphs to apply various impression management tactics in economic, social, and environmental disclosures of corporate reports. In this research, the use of graphs as an impression management tool has been determined through the corporate reports of 49 companies selected in the BIST (Borsa Istanbul) Sustainability Index of 2018 and 2019, Turkey. In total, 502 graphs in the reports of the selected companies were examined by descriptive analysis and the findings were statistically tested. According to the results, it was found that companies use both presentational enhancement and obfuscation as impression management tactics in corporate reports. This study helps to fill the research gap in the absence of an empirical study conducted in an emerging economy, Turkey. Additionally, it is the first study that focuses on graphs with impression management tactics that has ever been conducted in Turkey.
Keywords: impression management; enhancement; obfuscation; corporate reports; graphs; STRATEGIES; DISCLOSURE; PERFORMANCE; COMPANIES; INSIGHTS; Science & Technology - Other Topics; Environmental Sciences & Ecology